2020
DOI: 10.1038/s41598-020-78916-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of internet use and electronic game-play on academic performance of Australian children

Abstract: This study examined the association of internet use, and electronic game-play with academic performance respectively on weekdays and weekends in Australian children. It also assessed whether addiction tendency to internet and game-play is associated with academic performance. Overall, 1704 children of 11–17-year-olds from young minds matter (YMM), a cross-sectional nationwide survey, were analysed. The generalized linear regression models adjusted for survey weights were applied to investigate the association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
28
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 35 publications
3
28
0
6
Order By: Relevance
“…(Table1). We reported that 58% of children who played video games in present study their age group belonged to 12-14 years old agreeing with Islam et.al which found that average children age were 15.38% among player [23]. Concerning gender about 74% among played children were boys agreeing with studies suggesting that there are gender differences in time spent playing video games and preferred content [24,25].…”
supporting
confidence: 82%
See 2 more Smart Citations
“…(Table1). We reported that 58% of children who played video games in present study their age group belonged to 12-14 years old agreeing with Islam et.al which found that average children age were 15.38% among player [23]. Concerning gender about 74% among played children were boys agreeing with studies suggesting that there are gender differences in time spent playing video games and preferred content [24,25].…”
supporting
confidence: 82%
“…(Table 2). Our study found that 18% of fathers graduated from college agreeing with Islam et al, reporting 33.2% primary career's highest level of education [23]. Concerning family income, 66% of played children family were from low socio-economic status agreeing with Hasting et al, which reported that most of the family income in middle-class (annual family income) [27].Concerning parent educational level the present study showed a highly significant association between parent educational levels with their children school achievement.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…We also find large coefficient values at the 75 th and 90 th percentile of screen time (10 and 8 minutes respectively). This analysis indicates that financial hardship impacts children's screen time more at the upper end of the distribution, which is where additional time spent on screens is arguably more harmful (Islam, Biswas, & Khanam, 2020;Twenge & Campbell, 2018) 4.4 Heterogeneity by type of screen time Different types of screen time have differential impacts on children's health and development.…”
Section: Unconditional Quantile Regressionsmentioning
confidence: 99%
“…Thus, adolescents have a high risk of experiencing problems due to addictive symptoms such as imperfect identity integration, unpredictable behavior and its consequences, and neurobiological immaturity ( Steinhausen and Metzke, 2001 ; Kuss et al, 2013 ; Torres-Rodríguez et al, 2018 , 2019 ). With recent surveys showing that 75% of male adolescents in highly developed Western countries immerse themselves in game use weekly ( Islam et al, 2020 ) and 85% of Korean adolescents use games about 90 min daily ( Cui et al, 2018 ; Korean Creative Content Agency, 2020 ), game use among adolescents is approaching danger and is threatening future social balance ( Hawi et al, 2018 ). In order to understand the increase in the use of addictive games among adolescents and their effects, it is necessary to understand the mechanisms of adolescents’ gaming behavior.…”
Section: Introductionmentioning
confidence: 99%